THE BENEFITS OF NURSE-LED SUPPORT GROUPS FOR PATIENTS AND FAMILIES - Taraf Munished A Aldhafeeri, Sultan Razqan M Almutairi, Yosef Mohammed Alowaymer, Wedad Ali Ahmed Khawaji, Fowziah Daher Alanzy, Mona Saleh Alwabel, Malik Awadallah Q Almutairi,; Fahad Dakhilullah Almutairi, Hamad Hadi M Almutairi, Talal Mohammed Alanazi, Abdulaziz Dakhilullah Almutairi, Faris Suliman Alrumikan (Chelonian Research Foundation, 2022)
The COVID-19 pandemic has worsened the effects of a patient being admitted to critical care facilities, resulting in families experiencing a greater number of psychological problems compared to prior years. Therefore, it is important for nurses and other clinicians to stay updated on treatments that provide assistance to the relatives of critical care patients. The objective is to provide empirical data on the efficacy of family interventions led by nurses in adult critical care environments and their impact on family outcomes. The search included a thorough examination of pertinent databases such as PubMed, Scopus, as well as the Cochrane Library. Additionally, citations in relevant papers were scrutinized. The study included research on the effects of nurse-led interventions in adult critical care settings, examining family outcomes. Both qualitative and quantitative approaches were considered, allowing for the inclusion of results from either approach in the mixed method synthesis. The assessment of the article's quality was conducted by three writers using the critical evaluation methods provided by the Joanna Briggs Institute. The categories exhibited variation in terms of their constituent parts, mode of delivery, and the resulting effects on families. Nurse-led therapies, such as educational interventions using digital storytelling, a packaged approach, informative nursing services, and nurse-driven emotional support, yielded modest to moderate enhancements in family outcomes. The two included studies that examined family visits in the ICU found that this technique had no significant impact on family outcomes. The variations in the intervention components, instruments, and results assessed in this analysis demonstrate the wide range of family requirements, and the existence of several treatments that have previously been devised to enhance family well-being in critical care environments. Based on the data, it is indicated that family outcomes may be enhanced by multidisciplinary nurse-led interventions. Keywords: Critical care, Family-centered care, Family effects, Nursing action, Review.